Sebaceous Adenoma Case in a Golden Retriever Dog - Palagan Senopati Sewoyo; Willy Moris Nainggolan (Journal of Applied Veterinary Science And Technology, 2023)
Background: Sebaceous adenoma is a benign tumour originating from the skin's sebaceous glands. These tumours can arise in older and middle-aged dogs, typically on various body parts, head, and extremities. The tumours can manifest as either lumps or ulcers. Ulcers may develop when the animal scratches the tumour mass. Purpose: Increase the insight and ability of veterinary practitioners in diagnosing and providing information regarding the treatment of sebaceous adenomas. Case: A nine-year-old Golden retriever dog was brought to the Bali Veterinary Clinic with a complaint of a lateral wound on the face skin of the right eye. Anamnesis revealed that the initial wound was a lump. Clinical examination showed a yellowish ulcer with a 2 cm diameter. Case Management: A hematology examination indicated mild anemia in the dog, while blood biochemistry revealed no abnormalities. Cytology confirmed that the ulcer was a sebaceous adenoma. The owner declined surgery for their pet, so treatment involved applying Bioplacenton® gel to the ulcer area to prevent further infection and accelerate wound healing. Conclusion: In this case, the ulcer wound can be concluded as a sebaceous adenoma. This tumour is benign and harmless, but it is advisable to remove the tumour mass if it impairs the animal's activity and prevents potential secondary infection.